Introduksi Teknologi Pembuatan Konsentrat Dan Aplikasi Manajemen Good Farming Practice Pada Kelompok Ternak Kambing Perah Mon Bubhouh - Armia, Yasser; Mustofa, Achmad; Allaily, Allaily; Koesmara, Hendra; ammar; Ariga, Ali Makmur (JURNAL PENGABDIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (JP3L), 2023)
The Mon Bubhouh Dairy Goat Farming Group is one of the dairy goat farms in Aceh Besar Regency, more precisely in Gampong Meunasah Mon. The feed aspect is one of the causes of the lack of milk production on this farm. Group members' knowledge of feed that suits the nutritional needs of dairy livestock is still shallow. There needs to be an approach from the parties so that the sustainability of this livestock group can be realized. In this community service, the community will be introduced to the procedure for making cheap and high-quality feed, namely by utilizing fermentation technology in making concentrate using tofu dregs waste as the main raw material. Furthermore, the community was also initiated into the aspects of proper livestock cultivation. This relates to cage sanitation, mating methods and even lactation planning.